Flake-like composition and method for producing the flake-like composition

JP7633638B2Active Publication Date: 2025-02-20NIPPON FIBER CORP
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2020137028
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-08-14
Publication Date
2025-02-20
Estimated Expiration
2040-08-14

AI Technical Summary

Benefits of technology

【0007】 本発明によれば、石炭を燃料とする火力発電所から排出される廃棄物をより有効に利用できるフレーク状組成物、フレーク状組成物の製造方法を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007633638000001
    Figure 0007633638000001
  • Figure 0007633638000002
    Figure 0007633638000002
  • Figure 0007633638000003
    Figure 0007633638000003
Patent Text Reader

Abstract

To provide a flaky composition which can more efficiently utilize, waste discharged from a heat power station which uses as fuel, coal, and a production method of the flaky composition.SOLUTION: There is provided a flaky composition which includes, as a raw material, waste discharged from a heat power station which uses as fuel, coal.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a flaky composition and a method for producing the flaky composition. [Background technology]

[0002] Since the Great East Japan Earthquake, the operation of nuclear reactors has been restricted, and the proportion of thermal power generation in the energy supply has increased. Thermal power generation includes power generation using coal as fuel, such as coal-fired thermal power plants, fluidized bed combustion furnaces, and integrated coal gasification combined cycle (IGCC). In IGCC, coal gasification gas is used as fuel to drive a gas turbine to generate electricity, and exhaust heat from the gas turbine is recovered to generate steam, which is then used to drive a steam turbine to generate electricity.

[0003] However, currently, the only established utilization method for waste generated during the operation of coal-fired thermal power plants, fluidized bed combustors, IGCC and other thermal power plants that generate electricity using coal as fuel is to crush and otherwise process the waste and use it as aggregate for cement (see Patent Document 1). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2017-014052 A Summary of the Invention [Problem to be solved by the invention]

[0005] The present invention has been made in consideration of the above-mentioned problems, and aims to provide a flake composition that can more effectively utilize waste discharged from coal-fired thermal power plants, and a method for producing the flake composition. [Means for solving the problem]

[0006] In order to solve the above problems, the flake composition according to the present invention is characterized in that it contains waste material discharged from a thermal power plant that uses coal as fuel as a raw material. Effect of the Invention

[0007] According to the present invention, it is possible to provide a flake composition that allows more effective utilization of waste discharged from thermal power plants that use coal as fuel, and a method for producing the flake composition. [Brief description of the drawings]

[0008] [Figure 1] FIG. 2 is a diagram showing the mixing ratio (mass%) of raw materials according to an embodiment. [Diagram 2] FIG. 2 is a diagram showing the component composition of waste materials and the like used as raw materials in the examples. [Diagram 3] FIG. 2 is a diagram showing the component composition of raw materials according to an embodiment. [Figure 4] FIG. 2 is a diagram showing an outline of an electric furnace used in producing a flake composition from raw materials according to the examples. [Diagram 5] FIG. 2 is a table showing the temperature conditions and the experimental results (spinnability and flake properties) when the raw materials according to the examples were melted in an electric furnace. [Figure 6] 1 is a graph showing a time series of temperature changes when raw materials according to an embodiment are melted in an electric furnace. [Figure 7] FIG. 2 is a diagram showing a specific component composition of a raw material according to an embodiment. [Figure 8] FIG. 2 is an enlarged view (microscope photograph) of a flake composition obtained from the raw material according to the embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] [Background explanation] The inventors conducted experiments to produce fibers from raw materials containing waste, in order to effectively utilize waste (hereinafter simply referred to as waste) discharged from coal-fired thermal power plants (for example, WO2017 / 070748). In the production of fibers, raw materials containing waste are placed in a Tammann tube suspended in an electric furnace, and the raw materials are melted at a predetermined temperature. Next, the molten material (molten raw materials) that flows out from a hole (diameter 2mm to 3mm) provided in the center of the bottom of the Tammann tube is drawn out in a thin stream to produce fibers. When producing fiber from raw materials including waste in this way, the molten material solidifies and falls into a spherical shape from a hole provided in the center of the bottom of the Tammann tube, and it was found that when the spherical material was crushed, a plate-like or scaly composition (hereinafter also referred to as a flake-like composition) with an amorphous structure (hereinafter, amorphous is also referred to as non-crystalline) was obtained. The spherical material was crushed by hitting it with an iron hammer. Hereinafter, an embodiment for obtaining a flake composition from raw materials including waste will be described.

[0010] In the following explanation, melt spinning refers to a technique in which the raw material is melted by heat, discharged from a hole (through hole) formed in a die, turned into a fiber-like material, and then cooled and solidified. Spinnability refers to the generation of fibers by the melt dropping in a fiber-like form from the above-mentioned hole (diameter 2 mm to 3 mm), or the insertion of a thin rod into the hole, welding the melt to the tip of the rod, and the removal of the rod from the hole, pulling the melt out in a fiber-like form to generate fibers. In this embodiment, the flake composition refers to a plate-like or scaly composition having an amorphous structure. In consideration of the use of the flake composition (for example, glitter pigment, paint, lining, covering material, reinforcing material, etc.), it is preferable that the thickness of the flake composition is within the range of 1 μm to 80 μm, and the length of the long side is within the range of 5 μm to 1200 μm. Here, the thickness of the flake composition refers to the thickness of the thickest part of the flake composition. In addition, the long side of the flake composition refers to the length of the long side of a rectangular flake composition. The method of measuring the thickness and long side of the flake composition will also be described later with reference to FIG. 8. The term "flaky" refers to the fact that the molten material solidifies and turns into spheres that fall through a hole (diameter 2 mm to 3 mm) provided in the center of the bottom of the Tammann tube, and that the spheres are crushed to obtain a flake-like composition.

[0011] Furthermore, in the following description, Fe2O3 is referred to as the F component, and the Fe2O3 content is also written as [F]. SiO2 is referred to as the S component, and the SiO2 content is also expressed as [S]. Al2O3 is referred to as component A, and the content of Al2O3 is also written as [A]. CaO is referred to as the C component, and the CaO content is also written as [C].

[0012] [Embodiment] The raw material for producing the flake composition according to the present embodiment includes waste materials discharged from coal-fired thermal power plants (hereinafter, also simply referred to as waste materials). Here, the thermal power plants include coal-fired thermal power plants, fluidized bed combustion furnaces, and integrated coal gasification combined cycle (hereinafter, also referred to as IGCC (Integrated Coal Gasification Combined Cycle)).

[0013] The raw material of the flake composition is composed mainly of SiO2 and Al2O3, the ratio of Al2O3 to the total of SiO2 and Al2O3 in the raw material is within a specific range, and further contains a specific amount of CaO.

[0014] The raw material for the flaky composition according to this embodiment preferably has a total content of SiO2 and Al2O3 of 45% by mass or more and 75% by mass or less, more preferably 46% by mass or more and 63% by mass or less. When the total of [S] and [A] is less than 45% by mass or more than 75% by mass, the melting temperature of the raw material becomes high or the viscosity of the melt becomes high, so that the melt does not flow out from the hole (diameter 2 mm to 3 mm) provided at the bottom of the Tammann tube, and flake properties may not be obtained.

[0015] As long as the components in the raw material are blended to satisfy the above-mentioned composition conditions, the flake composition according to this embodiment can be obtained without any restrictions on the origin of the raw material. As the raw material for the flake composition according to this embodiment, it is preferable to use waste materials discharged from coal-fired thermal power plants (e.g., coal-fired thermal power plants, fluidized bed combustion furnaces, integrated gasification combined cycle (IGCC), etc.). The waste materials discharged from coal-fired thermal power plants contain Fe2O3, Al2O3, and SiO2 as main components, which is why they are suitable for obtaining the flake composition according to this embodiment and can reduce raw material costs.

[0016] The flake composition according to this embodiment does not exclude the inclusion of unavoidable impurities. Major unavoidable impurities include MgO, Na2O, K2O, TiO2, and CrO2.

[0017] In this embodiment, there is no substantial difference between the component ratio (mass ratio) of the raw material and the component ratio (mass ratio) of the flake composition produced by melting the raw material. Therefore, the component ratio of the raw material can be regarded as the component ratio of the flake composition produced by melting the raw material.

[0018] The flake composition according to the present embodiment is rich in amorphousness, and therefore the flake composition hardly loses strength due to separation of the crystalline phase / amorphous phase, making it possible to obtain a flake composition with high strength. Here, the degree of amorphousness, which is a measure of amorphousness, is calculated from an X-ray diffraction (XRD) spectrum by the following formula (1). Amorphousness (%)=[la / (la+lc)]×100...(1) In the above formula (1), la and lc are as follows, respectively. la: the integral of the scattering intensity of the amorphous halo. lc: the integral value of the scattering intensity of the crystalline peak when the flake composition is subjected to X-ray diffraction analysis. The degree of amorphization of the flake composition according to this embodiment, depending on the composition, is usually 90% or more. The degree of amorphization of the flake composition can reach 95% or more at high values, and at the highest value, it is essentially composed of only an amorphous phase. Here, "essentially composed of only an amorphous phase" means that only an amorphous halo is observed in the X-ray diffraction spectrum, and no crystalline peak is observed. EXAMPLES

[0019] Examples will be described below. In the following test examples, waste materials discharged from coal-fired thermal power plants were mixed at a predetermined mixing ratio (mass%) as the raw material for the flake composition. The waste materials used were those discharged from domestic coal-fired thermal power plants. The mixing ratios of the raw materials S1 to S14 will be explained below with reference to FIG. 1. In FIG. 1, IGCC slag indicates waste materials from domestic integrated coal gasification combined cycle (IGCC) plants, and FA1 to FA8 indicate waste materials from domestic coal-fired thermal power plants (FA1 to FA8 are different power plants). BA1 indicates basalt.

[0020] Raw material S1 is a mixture of 20% by mass of waste discharged from an integrated coal gasification combined cycle (IGCC), 10% by mass of basalt, 40% by mass of waste discharged from a coal-fired power plant FA1, and 30% by mass of waste C discharged from a coal-fired power plant FA2.

[0021] The raw material S2 is a mixture of 50% by mass of waste discharged from an integrated coal gasification combined cycle (IGCC) and 50% by mass of waste discharged from a coal-fired power plant FA2.

[0022] The raw material S3 is a mixture of 75 mass % waste discharged from an integrated coal gasification combined cycle (IGCC) and 25 mass % waste discharged from a coal-fired power plant FA2.

[0023] The raw material S4 is a mixture of 90 mass % of waste discharged from an integrated coal gasification combined cycle (IGCC) and 10 mass % of waste discharged from a coal-fired power plant FA2.

[0024] The raw material S5 is a mixture of 90 mass % of waste discharged from an integrated coal gasification combined cycle (IGCC) and 10 mass % of waste discharged from a coal-fired power plant FA2.

[0025] The raw material S6 is mixed with waste discharged from a coal-fired power plant FA5 at a ratio of 100 mass %.

[0026] Raw material S7 is a mixture of 30% by mass waste from an integrated coal gasification combined cycle (IGCC), 5% by mass basalt, 15% by mass waste from a coal-fired power plant FA2, and 50% by mass waste from a coal-fired power plant FA7.

[0027] The raw material S8 is a mixture of 50% by mass of waste discharged from an integrated coal gasification combined cycle (IGCC) and 50% by mass of waste discharged from a coal-fired power plant FA3.

[0028] Raw material S9 is a mixture of 20% by mass of waste discharged from an integrated coal gasification combined cycle (IGCC), 10% by mass of waste discharged from a coal-fired power plant FA2, 30% by mass of waste discharged from a coal-fired power plant FA3, and 40% by mass of waste discharged from a coal-fired power plant FA4.

[0029] Raw material S10 is a mixture of 25% by mass of waste discharged from an integrated coal gasification combined cycle (IGCC), 10% by mass of waste discharged from a coal-fired power plant FA4, and 65% by mass of waste discharged from a coal-fired power plant FA6.

[0030] Raw material S11 is a mixture of 70% by mass of waste discharged from coal-fired power plants FA3, 10% by mass of waste discharged from coal-fired power plants FA4, 10% by mass of waste discharged from coal-fired power plants FA6, and 10% by mass of waste discharged from coal-fired power plants FA7.

[0031] Raw material S12 is a mixture of 10% by mass of waste discharged from an integrated coal gasification combined cycle (IGCC), 16% by mass of waste discharged from a coal-fired power plant FA2, 36% by mass of waste discharged from a coal-fired power plant FA3, and 37% by mass of waste discharged from a coal-fired power plant FA6.

[0032] Raw material S13 is a mixture of 25% by mass of waste discharged from an integrated coal gasification combined cycle (IGCC), 10% by mass of waste discharged from a coal-fired power plant FA4, and 65% by mass of waste discharged from a coal-fired power plant FA6.

[0033] Raw material S14 is a mixture of 7% by mass of waste discharged from coal-fired power plant FA4, 18% by mass of waste discharged from coal-fired power plant FA5, and 75% by mass of waste discharged from coal-fired power plant FA8.

[0034] In this embodiment, the components of the raw waste and basalt (waste, etc.) were analyzed by X-ray fluorescence analysis. An X-ray fluorescence analyzer (Philips PW2404) from Philips Japan Ltd. was used for the analysis, and the components of the waste, etc. were analyzed with the sample chamber of the X-ray fluorescence analyzer in a vacuum state. Figure 2 shows the component composition of the waste, etc. Note that in the following, 0 mass% means a trace amount that cannot be measured, and does not mean strictly "0".

[0035] Waste discharged from a domestic integrated coal gasification combined cycle (IGCC) plant contains 9% by mass [F], 54% by mass [S], 11% by mass [A], 17% by mass [C], and other contents of 9% by mass.

[0036] Basalt (Basalt BA1) contains 19 mass% [F], 46 mass% [S], 11 mass% [A], 17 mass% [C], and other contents of 6 mass%.

[0037] The waste discharged from domestic coal-fired power plant FA1 contains 13% by mass [F], 57% by mass [S], 17% by mass [A], 6% by mass [C], and other contents of 7% by mass.

[0038] The waste discharged from the domestic coal-fired power plant FA2 contains 55% by mass [F], 35% by mass [S], 5% by mass [A], 2% by mass [C], and other contents of 3% by mass.

[0039] The waste discharged from the domestic coal-fired power plant FA3 contains 2% by mass of [F], 62% by mass of [S], 27% by mass of [A], 3% by mass of [C], and other contents of 5% by mass.

[0040] The waste discharged from the domestic coal-fired power plant FA4 contains 97% by mass of [F], 0% by mass of [S], 0% by mass of [A], 0% by mass of [C], and other contents of 3% by mass.

[0041] The waste discharged from the domestic coal-fired power plant FA5 contains 21% by mass [F], 35% by mass [S], 12% by mass [A], 22% by mass [C], and other contents of 10% by mass.

[0042] The waste discharged from domestic coal-fired power plant FA6 contains 1% by mass [F], 73% by mass [S], 22% by mass [A], 0% by mass [C], and other contents of 4% by mass.

[0043] The waste discharged from the domestic coal-fired power plant FA7 contains 1% by mass [F], 19% by mass [S], 17% by mass [A], 55% by mass [C], and other contents of 8% by mass.

[0044] The waste discharged from the domestic coal-fired power plant FA8 contains 0 mass% [F], 34 mass% [S], 13 mass% [A], 42 mass% [C], and other contents of 11 mass%.

[0045] Fig. 3 is a diagram showing the composition of raw materials S1 to S14 according to the embodiment. The composition shown in Fig. 3 was calculated from the mixing ratio of each raw material S1 to S14 in Fig. 1 and the composition of waste, etc. in Fig. 2. Note that the total does not necessarily add up to 100% because the figures are rounded off to the nearest whole number.

[0046] Raw material S1 contains 26 mass% [F], 49 mass% [S], 12 mass% [A], 8 mass% [C], and other contents of 6 mass%.

[0047] Raw material S2 contains 32 mass% [F], 45 mass% [S], 8 mass% [A], 10 mass% [C], and other contents of 6 mass%.

[0048] Raw material S3 contains 21 mass% [F], 49 mass% [S], 10 mass% [A], 13 mass% [C], and other contents of 8 mass%.

[0049] Raw material S4 contains 14 mass% [F], 52 mass% [S], 10 mass% [A], 16 mass% [C], and other contents of 8 mass%.

[0050] Raw material S5 contains 14 mass% [F], 52 mass% [S], 10 mass% [A], 16 mass% [C], and other contents of 8 mass%.

[0051] Raw material S6 contains 21 mass% [F], 35 mass% [S], 12 mass% [A], 22 mass% [C], and other contents of 10 mass%.

[0052] Raw material S7 contains 12 mass% [F], 33 mass% [S], 13 mass% [A], 34 mass% [C], and other contents of 8 mass%.

[0053] Raw material S8 contains 6 mass% [F], 58 mass% [S], 19 mass% [A], 10 mass% [C], and other contents of 7 mass%.

[0054] Raw material S9 contains 47 mass% [F], 33 mass% [S], 11 mass% [A], 5 mass% [C], and other contents of 4 mass%.

[0055] Raw material S10 contains 13 mass% [F], 61 mass% [S], 17 mass% [A], 5 mass% [C], and other contents of 4 mass%.

[0056] Raw material S11 contains 12 mass% [F], 53 mass% [S], 23 mass% [A], 8 mass% [C], and other contents of 4 mass%.

[0057] Raw material S12 contains 11 mass% [F], 60 mass% [S], 20 mass% [A], 3 mass% [C], and other contents of 6 mass%.

[0058] Raw material S13 contains 13 mass% [F], 61 mass% [S], 17 mass% [A], 5 mass% [C], and other contents of 4 mass%.

[0059] Raw material S14 contains 11 mass% [F], 32 mass% [S], 12 mass% [A], 36 mass% [C], and other contents of 9 mass%.

[0060] FIG. 4 is a diagram showing an outline of an electric furnace 1 used when obtaining a flake composition from the raw material according to the embodiment. In this embodiment, the electric furnace 1 shown in FIG. 4 was used to obtain a flake composition. The electric furnace 1 is a cylinder having a height H of 60 cm and an outer diameter D of 50 cm, with a through hole 4 having an inner diameter d of 10 cm formed in the center. A Tammann tube 2 having an inner diameter of 2.1 cm and a length of 10 cm is suspended in the through hole 4 by a hanging rod 3. Any of the raw materials S1 to S14 is charged in the Tammann tube 2. A hole having a diameter of 2 mm is provided in the center of the bottom of the Tammann tube 2, and when the raw materials S1 to S14 are melted by heating, they flow out from the hole provided in the bottom of the Tammann tube due to gravity. The melted raw materials that flow out are cooled and solidified by contact with the outside air. The melted raw materials that flow out from the bottom of the Tammann tube (hereinafter also referred to as molten material) are solidified by being rapidly cooled. Here, the molten material that flows out is cooled so rapidly that the flake composition is substantially composed of only amorphous matter.

[0061] The electric furnace 1 is heated according to a predetermined heating program, and it has been confirmed in advance that the temperature (° C.) of the molten material in the Tammann tube 2 follows a temperature approximately 50° C. lower than the temperature inside the furnace.

[0062] Fig. 5 is a table showing the temperature conditions and experimental results (spinnability and flake property) when raw materials S1 to S14 were melted in an electric furnace, and Fig. 6 is a graph showing the temperature change over time when raw materials S1 to S14 were melted in an electric furnace.

[0063] Example 1 After the raw material S1 was set in the Tammann tube, the temperature in the furnace was raised from room temperature (25°C) to about 1400°C (raw material temperature 1350°C), and then held at about 1400°C for 1 hour (annealing treatment). After that, the temperature in the furnace was raised from about 1400°C (raw material temperature 1350°C) to about 1450°C (raw material temperature 1400°C) over 1 hour, while the melt was allowed to flow out from the hole provided at the bottom of the Tammann tube by gravity. From the hole provided at the center of the bottom of the Tammann tube, the melt solidified into a sphere fell, and the melt continued to fall in a fibrous form, generating a fiber (spinnability "good"). In addition, a flake-shaped composition could be obtained by crushing the solidified spheres (flakeability "good"). In this embodiment, the solidified spheres were crushed by hitting with an iron hammer. In the following Examples 2 to 7, the molten material solidified into spheres and was crushed by hitting with an iron hammer.

[0064] Example 2 After the raw material S2 was set in the Tammann tube, the temperature in the furnace was raised from room temperature (25°C) to about 1375°C (raw material temperature 1325°C), and then held at about 1375°C for 1 hour (annealing treatment). After that, the temperature in the furnace was raised from about 1375°C (raw material temperature 1325°C) to about 1450°C (raw material temperature 1400°C) over 15 hours, while the melt was allowed to flow out of the hole at the bottom of the Tammann tube by gravity. The melt solidified into a sphere and fell from the hole at the center of the bottom of the Tammann tube, and the melt then fell in a fibrous form to generate fibers (spinnability "good"). In addition, the solidified spheres of the melt were crushed to obtain a flake-like composition (flakeability "good").

[0065] Example 3 After the raw material S3 was set in the Tammann tube, the temperature in the furnace was raised from room temperature (25°C) to about 1375°C (raw material temperature 1325°C), and then held at about 1375°C for 1 hour (annealing treatment). After that, the temperature in the furnace was raised from about 1375°C (raw material temperature 1325°C) to about 1450°C (raw material temperature 1400°C) over 15 hours, while the melt was allowed to flow out of the hole at the bottom of the Tammann tube by gravity. The melt solidified into a sphere and fell from the hole at the center of the bottom of the Tammann tube, and the melt then fell in a fibrous form to generate fibers (spinnability "good"). In addition, the solidified spheres of the melt were crushed to obtain a flake-like composition (flakeability "good").

[0066] Example 4 After the raw material S4 was set in the Tammann tube, the temperature in the furnace was raised from room temperature (25°C) to about 1375°C (raw material temperature 1325°C), and then held at about 1375°C for 1 hour (annealing treatment). After that, the temperature in the furnace was raised from about 1375°C (raw material temperature 1325°C) to about 1400°C (raw material temperature 1350°C) over 8 hours, while the melt was allowed to flow out of the hole at the bottom of the Tammann tube by gravity. The melt solidified into a sphere and fell from the hole at the center of the bottom of the Tammann tube, and the melt then fell in a fibrous form to generate fibers (spinnability "good"). In addition, the solidified spheres of the melt were crushed to obtain a flake-like composition (flakeability "good").

[0067] Example 5 After the raw material S5 was set in the Tammann tube, the temperature in the furnace was raised from room temperature (25°C) to about 1350°C (raw material temperature 1300°C) (without annealing treatment), and the temperature in the furnace was raised from about 1350°C (raw material temperature 1300°C) to about 1400°C (raw material temperature 1350°C) over 2 hours while the melt was allowed to flow out of the hole at the bottom of the Tammann tube by gravity. The melt solidified into a sphere and fell from the hole at the center of the bottom of the Tammann tube, but the melt did not fall in a fibrous form and no fibers were produced (spinnability "x"). In addition, a flake-like composition could be obtained by crushing the solidified spheres (flakeability "good").

[0068] Example 6 After the raw material S6 was set in the Tammann tube, the temperature in the furnace was raised from room temperature (25°C) to about 1375°C (raw material temperature 1325°C), and then held at about 1375°C for 1 hour (annealing treatment). After that, the temperature in the furnace was raised from about 1375°C (raw material temperature 1325°C) to about 1400°C (raw material temperature 1350°C) over 5 hours, while the melt was allowed to flow out of the hole at the bottom of the Tammann tube by gravity. The melt solidified into a sphere and fell from the hole at the center of the bottom of the Tammann tube, and the melt continued to fall in the form of fiber, generating fiber (spinnability "good"). In addition, the solidified spheres of the melt were crushed to obtain a flake-like composition (flakeability "good").

[0069] Example 7 After the raw material S7 was set in the Tammann tube, the temperature in the furnace was raised from room temperature (25°C) to about 1375°C (raw material temperature 1325°C), and then held at about 1375°C for 1 hour (annealing treatment). After that, the temperature in the furnace was raised from about 1375°C (raw material temperature 1325°C) to about 1400°C (raw material temperature 1350°C) over 5 hours, while the melt was allowed to flow out of the hole at the bottom of the Tammann tube by gravity. The melt solidified into a sphere and fell from the hole at the center of the bottom of the Tammann tube, but the melt did not fall in a fibrous form and no fibers were produced (spinnability "x"). In addition, a flake-like composition could be obtained by crushing the solidified spheres (flakeability "good").

[0070] Comparative Example 1 After the raw material S8 was set in the Tammann tube, the temperature inside the furnace was raised from room temperature (25°C) to about 1375°C (raw material temperature 1325°C), and then held at about 1375°C for 1 hour (annealing treatment). Thereafter, the temperature inside the furnace was raised from about 1375°C (raw material temperature 1325°C) to about 1400°C (raw material temperature 1350°C) over 5 hours, while the melt was allowed to flow out of the hole at the bottom of the Tammann tube by gravity. The melt did not solidify and become spherical (flaky property "x") from the hole at the bottom center of the Tammann tube, and the melt did not fall in the form of fibers (spinnability "x").

[0071] Comparative Example 2 After the raw material S9 was set in the Tammann tube, the temperature inside the furnace was raised from room temperature (25°C) to about 1375°C (raw material temperature 1325°C), and then held at about 1375°C for 1 hour (annealing treatment). Thereafter, the temperature inside the furnace was raised from about 1375°C (raw material temperature 1325°C) to about 1400°C (raw material temperature 1350°C) over 5 hours, while the melt was allowed to flow out of the hole at the bottom of the Tammann tube by gravity. The melt did not solidify and become spherical from the hole at the center of the bottom of the Tammann tube (flaking property "x"), and the melt did not fall in the form of fibers (spinnability "x").

[0072] Comparative Example 3 After the raw material S10 was set in the Tammann tube, the temperature inside the furnace was raised from room temperature (25°C) to about 1375°C (raw material temperature 1325°C), and then held at about 1375°C for 1 hour (annealing treatment). After that, the temperature inside the furnace was raised from about 1375°C (raw material temperature 1325°C) to about 1400°C (raw material temperature 1350°C) over 5 hours, while the melt was allowed to flow out of the hole at the bottom of the Tammann tube by gravity. The melt did not solidify and become spherical from the hole at the center of the bottom of the Tammann tube (flaking property "x"), and the melt did not fall in the form of fibers (spinnability "x").

[0073] Comparative Example 4 After the raw material S11 was set in the Tammann tube, the temperature inside the furnace was raised from room temperature (25°C) to about 1375°C (raw material temperature 1325°C), and then held at about 1375°C for 1 hour (annealing treatment). Thereafter, the temperature inside the furnace was raised from about 1375°C (raw material temperature 1325°C) to about 1400°C (raw material temperature 1350°C) over 5 hours, while the melt was allowed to flow out of the hole provided at the bottom of the Tammann tube by gravity. The melt did not solidify and become spherical from the hole provided at the center of the bottom of the Tammann tube (flaking property "x"), and the melt did not fall in the form of fibers (spinnability "x").

[0074] Comparative Example 5 After the raw material S12 was set in the Tammann tube, the temperature inside the furnace was raised from room temperature (25°C) to about 1375°C (raw material temperature 1325°C), and then held at about 1375°C for 1 hour (annealing treatment). Thereafter, the temperature inside the furnace was raised from about 1375°C (raw material temperature 1325°C) to about 1400°C (raw material temperature 1350°C) over 5 hours, while the melt was allowed to flow out of the hole provided at the bottom of the Tammann tube by gravity. The melt did not solidify and become spherical from the hole provided at the center of the bottom of the Tammann tube (flaking property "x"), and the melt did not fall in the form of fibers (spinnability "x").

[0075] Comparative Example 6 After the raw material S13 was set in the Tammann tube, the temperature inside the furnace was raised from room temperature (25°C) to about 1375°C (raw material temperature 1325°C), and then held at about 1375°C for 1 hour (annealing treatment). Thereafter, the temperature inside the furnace was raised from about 1375°C (raw material temperature 1325°C) to about 1400°C (raw material temperature 1350°C) over 5 hours, while the melt was allowed to flow out of the hole provided at the bottom of the Tammann tube by gravity. The melt did not solidify and become spherical from the hole provided at the center of the bottom of the Tammann tube (flaking property "x"), and the melt did not fall in the form of fibers (spinnability "x").

[0076] Comparative Example 7 After the raw material S14 was set in the Tammann tube, the temperature inside the furnace was raised from room temperature (25°C) to about 1375°C (raw material temperature 1325°C), and then held at about 1375°C for 1 hour (annealing treatment). Thereafter, the temperature inside the furnace was raised from about 1375°C (raw material temperature 1325°C) to about 1400°C (raw material temperature 1350°C) over 5 hours, while the melt was allowed to flow out of the hole provided at the bottom of the Tammann tube by gravity. The melt did not solidify and become spherical from the hole provided at the center of the bottom of the Tammann tube (flaking property "x"), and the melt did not fall in the form of fibers (spinnability "x").

[0077] (Consideration) As described above, in Examples 1 to 7 (raw materials S1 to S7), the flake property was rated as "good," in other words, a flake-like composition was obtained, whereas in Comparative Examples 1 to 7 (raw materials S8 to S14), the flake property was rated as "bad," in other words, a flake-like composition could not be obtained. In addition, in Example 5 where no annealing treatment was performed, the flake property was "good", in other words, a flaky composition was obtained, but in Comparative Examples 1 to 7, the annealing treatment was performed but the flake property was "bad", in other words, a flaky composition could not be obtained. This shows that, unlike fibers, annealing is not necessary to obtain a flaky composition.

[0078] Fig. 7 is a diagram showing the predetermined component compositions ([S]+[A], [A] / ([A]+[S]), [Ca]) of raw materials S1 to S14. From the table shown in Fig. 7, it is found that the raw material of the flake composition has a total content of SiO2 and Al2O3 ([S]+[A]) of preferably 45 mass% or more and 75 mass% or less, and more preferably 46 mass% or more and 63 mass% or less. In addition, it was found that the raw material of the flake composition according to this embodiment has a ratio of Al2O3 to the total of SiO2 and Al2O3 ([A] / ([A]+[S])) (mass ratio) in the range of 0.15 to 0.28. In addition, the raw material of the flake composition according to this embodiment has a CaO content [C] of 8 Mass% or more 36 It was found that the content was less than % by mass.

[0079] FIG. 8 is an enlarged view (microscope photograph) of the flake composition obtained from the raw material according to the embodiment. The inventors measured the thickness and the length of the long side of the flake composition obtained in Examples 1 to 8 with a microscope. Here, the thickness and the length of the long side of the flaky composition, which is rectangular in plan view, were visually measured with an ocular micrometer installed in the microscope. Here, the thickness of the flake composition was measured as the thickness of the flake composition at the thickest point. In addition, the length of the long side of the flake composition was measured as the length of the point corresponding to the long side of the rectangular flake composition. As a result of the measurement, it was found that the flake composition had a thickness in the range of 1 μm to 80 μm and a long side length in the range of 5 μm to 1200 μm, and is suitable for applications such as glitter pigments, paints, linings, covering materials, and reinforcing materials.

[0080] In addition, when the flake composition shown in Fig. 8 was analyzed by X-ray diffraction (XRD) spectrum, it was found that the flake composition was essentially composed of only amorphous matter. This is believed to be because the molten raw material, after flowing out of the hole provided in the center of the bottom of the Tammann tube 2, was rapidly cooled, causing the regular atomic arrangement to be lost and the composition became amorphous.

[0081] In addition, even if the raw material containing waste discharged from a thermal power plant using coal as fuel is melted and then solidified by cooling (including natural cooling), the solidified material can be melted again to form a fiber or flake-like composition, so it is considered to be useful regardless of the shape. In this case, too, the raw material contains SiO2, Al2O3, and CaO as components, and the total content of SiO2 and Al2O3 in the raw material is preferably 45% by mass or more and 75% by mass or less, and more preferably 46% by mass or more and 63% by mass or less. [Industrial Applicability]

[0082] The flake composition can be used as a luster pigment, paint, lining, covering material, or reinforcing material. [Explanation of symbols]

[0083] 1 Electric furnace 2. Tamman tube 3 Hanging rod 4 Openings D Electric furnace outer diameter H Electric furnace height d Electric furnace opening inner diameter

Claims

1. A flake-like composition obtained by crushing a molten and solidified raw material consisting only of waste discharged from a thermal power plant using coal as fuel and basalt, i) the raw material contains 33 to 52 mass% SiO2, 8 to 13 mass% Al2O3, 8 to 34 mass% CaO, and 12 to 32 mass% Fe2O3; ii) the total content of SiO 2 and Al 2 O 3 in the raw material is 46% by mass or more and 63% by mass or less; iii) the flake composition has a thickness in the range of 1 μm to 80 μm and a long side length in the range of 5 μm to 1200 μm; and iv) A flaky composition characterized in that it is amorphous.

2. 2. The flaked composition of claim 1, wherein the waste generated from a coal-fired thermal power plant includes waste generated from an integrated coal gasification combined cycle (IGCC).

3. a) The only raw materials used are waste and basalt from coal-fired power plants; i) the raw material contains 33 to 52 mass % SiO 2 , 8 to 13 mass % Al 2 O 3 , 8 to 34 mass % CaO, and 12 to 32 mass % Fe 2 O 3 , and ii) blending the raw material with waste discharged from a thermal power plant using coal as fuel and basalt so that the total content of SiO2 and Al2O3 in the raw material is 46 mass% or more and 63 mass% or less; b) a step of heating the raw material that has been subjected to the step a) to 1300°C or higher to melt it; A step of allowing the heated and molten material that has been subjected to the steps (c) and (b) to flow and fall through the forming hole to obtain a solidified material; (d) crushing the solidified material by impact.

4. The method for producing a flake composition according to claim 1, wherein the waste discharged from a thermal power plant using coal as fuel includes waste from an integrated coal gasification combined cycle (IGCC).

Citation Information

Patent Citations

  • Coal ash treating method

    JP1995145924A

  • Multifunctional fly ash and method of manufacturing the same

    JP2002336813A

  • Method of producing artificial aggregate

    JP2003238221A

  • Waste treatment agent and method for solidifying waste using the same, solidified product, water-permeable block and formwork therefor

    JP2004298866A

  • Burned ash granulated material and method for producing it

    JP2009270059A